T93. When should monitoring end? A case report. (May 2018) - Parikh, Pooja; Cheongsiatmoy, Justin; Shilian, Parastou; Gonzalez, Andres A.
Abstract : Introduction: Transcranial motor evoked potentials (TcMEP) is the preferred modality for monitoring corticospinal tract integrity during spine surgery. In practice, final TcMEPs are obtained immediately after rod placement, during washout, or during early stages of closing before administration of inhalational agents. This raises the question: "When should monitoring conclude?" We present a case of a 63-year male who underwent T8-L4 posterior fusion, T12-L2 laminectomy and L1 partial corpectomy. In this surgery, we performed intraoperative neurophysiological monitoring during the entire case through suturing of the skin. During the final stages of skin closure, both TcMEP and somatosensory (SSEP) signals decreased significantly in the bilateral lower extremities. The surgeons subsequently re-opened the incision site and discovered a large blood clot compressing the dura. Methods: Patient presented with severe back pain and workup revealed a pathological L1 fracture with cord compression. At the onset of the surgery, anesthesia administered total intravenous anesthesia and avoided neuromuscular blockade. We obtained SSEPs and TcMEPs continuously throughout the case. Evoked potentials were unchanged until the stapling of skin during final stages of closure when TcMEPs were suddenly lost in the bilateral tibialis, gastocnemius and intrinsic feet muscle and significantly decreased in the bilateral vastus muscles. Upper extremity TcMEPs were stable. Upon further monitoring, bilateral lower extremity SSEPs were lost as well. There were no changes in anesthetic regimen. After reporting these findings, the surgical team completed staple closure and performed a clinical examination after extubation. Results: During clinical examination, the patient demonstrated loss of motor function in bilateral lower extremities with preservation of movement in bilateral upper extremities. The patient was reintubated and repositioned to the prone position for wound exploration. Upon re-initiation of neuromonitoring, the bilateral lower extremity TcMEPs and SSEPs remained absent. Surgeons discovered the epidural blood clot compressing the ventral dura during wound exploration. After immediate evacuation of the hematoma, bilateral TcMEP signals returned in lower extremities, right greater than left. SSEPs also demonstrated partial recovery. Clinically, the patient woke up without deficit. Conclusion: Loss of bilateral TcMEPs alone or in combination with SSEP changes warrant immediate due diligence. In this case, early intervention prevented further damage to nerve roots affected by the expanding hematoma. Because significant changes in signals can occur at any time, neurophysiological monitoring should be performed until final closure.